Impact of acceptor splice site NAGTAG motif on exon recognition - Hujová, Pavla; Grodecká, Lucie; Souček, Přemysl; Freiberger, Tomáš (Molecular biology reports, 2019)
Pre-mRNA splicing is an essential step in gene expression, when introns are removed and exons joined by the complex of proteins called spliceosome. Correct splicing requires a precise exon/intron junction definition, which is determined by a consensual donor and acceptor splice site at the 5' and 3' end, respectively. An acceptor splice site (3'ss) consists of highly conserved AG nucleotides in positions E-2 and E-1. These nucleotides can appear in tandem, located 3 bp from each other. Then they are referred to as NAGNAG or tandem 3'ss, which can be alternatively spliced. NAG/TAG 3'ss motif abundance is extremely low and cannot be easily explained by just a nucleotide preference in this position. We tested artificial NAG/TAG motif's potential negative effect on exon recognition using a minigene assay. Introducing the NAG/TAG motif into seven different exons revealed no general negative effect on exon recognition. The only observed effect was the partial use of the newly formed distal 3'ss. We can conclude that this motif's extremely low preference in a natural 3'ss is not a consequence of the NAG/TAG motif's negative effect on exon recognition, but more likely the result of other RNA processing aspects, such as an alternative 3'ss choice, decreased 3'ss strength, or incorporating an amber stop codon.
Keywords: tandemové repetitivní sekvence; HeLa Cells; Base Sequence; terminační kodon; sestřih RNA; RNA Splicing; nukleotidy; introny; lidé; HeLa buňky; Introns; Tandem Repeat Sequences; RNA Splice Sites; Nucleotides; Exons; sekvence nukleotidů; Codon, Terminator; alternativní sestřih; exony; Alternative Splicing; místa sestřihu RNA; Humans